(3cJGH GdCdaGX GdcJGHjIs - (3YHO GdQMef Hf YjSi Hf MeGO GdgeOGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd JhajbfG HMeOg bGd YHO GdQMef Hf YSi Hf MeGO GdgeOGfi GdcGJH GdUfGYGJ eNJdaGJ hdgG OQLGJ eJaGhJGJ aefgG eG jQaY Ggdg s
(3BNQgG (B:s
(3aGdeQCI GdJi dG cMd ai YjfgG hGdSdJG GdJi dG NVGH HcajgG Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs